Abstracts of bioremediation of destroyed environment for ỉmpovement of productivity in agriculture, forestry and fisheries (Japan, 2005)
The frist objective of the meeting is to stimulate the students; the second one is share of the information obtained from the project among the participants in the meeting.
Keywords: Environmental protection,Bảo vệ môi trường